2018
DOI: 10.1111/ajt.14463
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sleeve gastrectomy improves renal transplant candidacy and posttransplant outcomes in morbidly obese patients

Abstract: Morbid obesity is a barrier to kidney transplantation due to inferior outcomes, including higher rates of new-onset diabetes after transplantation (NODAT), delayed graft function (DGF), and graft failure. Laparoscopic sleeve gastrectomy (LSG) increases transplant eligibility by reducing BMI in kidney transplant candidates, but the effect of surgical weight loss on posttransplantation outcomes is unknown. Reviewing single-center medical records, we identified all patients who underwent LSG before kidney transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 39 publications
0
72
0
3
Order By: Relevance
“…These patients pose a multidisciplinary challenge due to multiple comorbidities, use of immunosuppressive agents, risk of graft dysfunction or rejection, and history or current status as patients with insufficiency of 1 or more systems. Due to these limitations, such patients had been considered inoperable, but they are now beginning to enjoy the benefits of BS …”
Section: Discussionmentioning
confidence: 99%
“…These patients pose a multidisciplinary challenge due to multiple comorbidities, use of immunosuppressive agents, risk of graft dysfunction or rejection, and history or current status as patients with insufficiency of 1 or more systems. Due to these limitations, such patients had been considered inoperable, but they are now beginning to enjoy the benefits of BS …”
Section: Discussionmentioning
confidence: 99%
“…Use of bariatric surgery in morbidly obese transplant candidates was reported to be a safe and effective bridge to KT . Using direct matching for BMI at the time of transplantation, as well as for age, race, and allograft type, obese ESRD patients who underwent laparoscopic sleeve gastrectomy (LSG) and whose pretransplant BMI decreased from 41.5 ± 4.4 to 32.3 ± 2.9 kg/m 2 had similar posttransplant outcomes including perioperative complications, allograft, and patient survival at 1 year compared with non‐LSG recipients …”
Section: Obesity Management Among Patients On Dialysismentioning
confidence: 99%
“…42 Using direct matching for BMI at the time of transplantation, as well as for age, race, and allograft type, obese ESRD patients who underwent laparoscopic sleeve gastrectomy (LSG) and whose pretransplant BMI decreased from 41.5 ± 4.4 to 32.3 ± 2.9 kg/m 2 had similar posttransplant outcomes including perioperative complications, allograft, and patient survival at 1 year compared with non-LSG recipients. 43 For dialysis patients with sarcopenic obesity, therapeutic intervention to preserve muscle mass and reduce excess body fat is an ultimate goal for improving outcomes. 44 Data from randomized controlled trials have demonstrated that intradialytic resistance exercise training can improve muscle volume and enhance muscle strength and physical performance among HD patients.…”
Section: Ob E S It Y Manag Ement Among Patients On D Ialys Ismentioning
confidence: 99%
“…This is the case even when well‐conducted, prospective studies of intentional weight loss on short‐ and long‐term posttransplant outcomes are lacking. Successful transplantation listing after bariatric surgery has been reported in several studies; many of these are small case series, with 55%‐100% of those undergoing bariatric surgery being listed for, or receiving a kidney transplant during follow‐up …”
Section: Weight Management Options—from Lifestyle To Bariatric Surgerymentioning
confidence: 99%
“…Successful transplantation listing after bariatric surgery has been reported in several studies; many of these are small case series, with 55%-100% of those undergoing bariatric surgery being listed for, or receiving a kidney transplant during followup. [19][20][21][22][23][24] More modest weight loss has been recorded with lifestyle approaches including dietary intervention with or without exercise.…”
Section: And Transplant Listingmentioning
confidence: 99%